PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN PADA KANTOR PDAM KAB. BANTUL - Rahadian Nova Pradipta; Suhesti Ningsih; Muhammad Hasan Ma'ruf (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the influence of information technology utilization and human resource competence on the quality of financial statements at the Regional Water Company (PDAM) Office of Bantul Regency. The research is motivated by the crucial role of transparent, accountable, and reliable financial reporting in supporting accountability and public services, especially within regional government-owned enterprises (BUMD) such as PDAM. A quantitative approach was employed, using surveys of employees involved in the financial reporting process. The results indicate that the use of information technology has a significant positive effect on the quality of financial statements, particularly in accelerating reporting processes, increasing data accuracy, and minimizing errors. Furthermore, human resource competence also has a significant impact, where technical accounting knowledge, analytical skills, and employee integrity are key factors in producing high-quality financial reports. The study recommends ongoing training, improved information technology infrastructure, and strengthened inter-unit coordination to achieve better financial governance at PDAM Bantul.